Sheltering under a shield of love—A phenomenological–hermeneutic study of relatives' experiences in an acute neurological ward - Lærke Toft Hesselvig; Malene Beck; Charlotte Simony (Nursing Open, 2020)
Abstract Aim To investigate the lived experience of being a relative to a patient admitted to an acute neurological ward to bring knowledge of what is essential to them. Design The study takes a phenomenological–hermeneutic approach. Methods Data were gathered through six individual semi‐structured interviews with relatives from an acute neurological ward. A three‐levelled analysis and interpretation inspired by Paul Ricoeur's philosophy was applied. Results Two main themes were identified: To make yourself strong while feeling vulnerable inside and To live in a changed everyday life. Within these themes, the connection between the relatives and the patients appeared to be a relationship of love. In this relationship, the relatives experience existential vulnerability. The lives of relatives undergo a difficult upheaval, which is challenged by deep emotional feelings. However, to be able to be there for their loved ones they are sheltering under a shield of love.